Waste mobile phones: A survey and analysis of the awareness, consumption and disposal behavior of consumers in Australia. (1st December 2020) - Islam, Md Tasbirul; Dias, Pablo; Huda, Nazmul
Abstract: Electronic waste (e-waste) is one of the fastest-growing waste streams in the world and waste mobile phone (WMP) represents a significant portion of the stream. Consumer awareness, consumption, and disposal behavior are of importance to assist in the implementation the circular economy. In Australia, some 94% of the adult population has a mobile phone, and the only WMP collection and recycling program in the country - "MobileMuster" is operating under a voluntary scheme. This study reveals consumers' familiarity with the program, current consumption, and disposal behavior concerning mobile phones from a survey implemented in Sydney, Australia. In addition to descriptive analysis, statistical analysis (with the Chi-square test of independence and Multinomial Logistic Regression (MLR)) identifies factors that influenced the behaviors. The results show that only one-third of the respondents (32.42%) were aware of the program, and that there are 3.65 mobile phones in use per household, with an average possession lifespan of 3.17 years (including storage). Furthermore, there is a positive relationship between age and possession of mobile phones, and respondents discard or change their mobile phones while they were still working or repairable. The main reasons for disposing of mobile phones relate to them being either damaged/not functioning, lacking additional features, or having a backdated capacity. Storing (hoarding) mobile phones after active use was found predominant, and, more specifically, respondents aged 18–24 and 25–29 preferred to store their WMPs instead of taking them to collection points. The results reveal a need for environmental awareness-raising campaigns concerning WMPs recycling. Highlights: 67.58% of the consumers were unfamiliar with the national mobile recycling program. Average mobile phone in-use in Australia was 1.41 per capita. Average possession lifespan of mobile phones among consumers was 3.17 years. Damaged or not functioning was the main reason for changing old mobile phones. Storing mobile phones at home is widespread.